2006
DOI: 10.1016/j.ijsolstr.2005.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Inner mass impact damper for attenuating structure vibration

Abstract: The behaviors of a vibration system suppressed with an impact damper are investigated, where the impact damper is simplified as a combination of spring and viscous damping. The analytical theory for the optimal impact control algorithms for impact damper is developed, and the accurate expressions are derived for the optimal values of the impact damper damping and initial displacement in a single-degree-of-freedom structure. The relation between coefficient of restitution and impact damping ratio is obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…Figure 1 shows the decay of the amplitude of a spring's oscillation with an attached granular damper. Similar figures can be found in many publications on granular damping [15,[18][19][20][21][22][23][24][25][26][27][28][29][30] which have three characteristic features in common: (a) for large amplitude, the decay follows an almost linear function of time; (b) for small amplitude (large time) the decay is weak and (c) there is a rather sharp transition between both regimes. In our case, the figure shows the attenuation of a flat spring where the granular damper is a rectangular polycarbonate container of mass M = 434 g and length L = 4 cm in the direction of vibration and cross section 5 × 5 cm 2 , mounted on top of a flat spring (k = 24.4 Nm −1 ) and loaded with 37 steel balls (diameter 1 cm, total mass m = 149 g).…”
Section: Introductionsupporting
confidence: 86%
“…Figure 1 shows the decay of the amplitude of a spring's oscillation with an attached granular damper. Similar figures can be found in many publications on granular damping [15,[18][19][20][21][22][23][24][25][26][27][28][29][30] which have three characteristic features in common: (a) for large amplitude, the decay follows an almost linear function of time; (b) for small amplitude (large time) the decay is weak and (c) there is a rather sharp transition between both regimes. In our case, the figure shows the attenuation of a flat spring where the granular damper is a rectangular polycarbonate container of mass M = 434 g and length L = 4 cm in the direction of vibration and cross section 5 × 5 cm 2 , mounted on top of a flat spring (k = 24.4 Nm −1 ) and loaded with 37 steel balls (diameter 1 cm, total mass m = 149 g).…”
Section: Introductionsupporting
confidence: 86%
“…Several important structures such as helicopter rotor blades, turbine and compressor blades, windmill turbine blades and propeller blades can be modeled as rotating beams (Cheng and Xu, 2006;Stephen and Zhang, 2006). Therefore, the dynamic analysis of a rotating beam is an important research topic and several researchers have addressed this field.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was subsequently confirmed by Chen [23] and Butt [24]. Chetterjee and Malik [25], Collette [26], Semercigil [27], Cheng [28] and Li [29] determined the damping performance of impact dampers used in practical applications in their carefully prepared experiments. Ema and Marui [30] concluded that in the free decaying response of a spring mass system, the damping rate of the system increases with a corresponding increase in vibration amplitude.…”
Section: Introductionmentioning
confidence: 71%